The role of super-leadership in enhancing behavioral integrity (An Empirical study in the Federal Integrity Commission) - Alabedi, Ali Razzaq Chyad; Alattabi, Basim Abdulghni (International Journal of Psychosocial Rehabilitation, 2020)
The present research aims to investigate the impact of super-leadership on behavioral integrity in Federal Integrity Commission. to achieve the aim of the research, Was used the (descriptive-analytical) method was used, and the questionnaire was used as a main tool in data collection, as (300) questionnaires were distributed to a sample of employees in Federal Integrity Commission based on a random sample technique and (268) questionnaires were retrieved, which are valid for statistical analysis. The results show there is a statistically direct positive effect and significance of super-leadership on behavioral integrity. the researchers draw an overall conclusion from the research as a whole.